The effectiveness of formulation of brenuk botanical insecticide on Empoasca flavescens on tea - Odih Sucherman (Research Institute for Tea and Cinchona, 2013)
An experiment to find out the effectiveness of formulation of brenuk botanical insecticide on Empoasca flavescens on tea was carried out at Pasir Sarongge Experimental Garden, Research Institute for Tea and Cinchona, from Juni up to September 2012. The experiment was designed in randomized complete block design with eight treatments and three replications. The treatment was consist of: (1) brenuk insecticide at 0,5 litre of EC formulation/ha, (2) brenuk insecticide at 1,0 litre of EC formulation/ha, (3) brenuk insecticide at 1,5 litre of EC formulation/ha, (4) brenuk insecticide at 0,5 litre of WP formulation/ha, (5) brenuk insecticide at 1,0 litre of WP formulation/ha, (6) brenuk insecticide at 1,5 litre of WP formulation/ha, (7) marigold insecticide at 1,5 litre of EC formulation/ha, and (8) control. The water spray volume used was 300 litre/ha. The observation parameters were the attack intensity of E. flavescens, the population of E. flavescens on the production of tea shoots. The experiment result indicated that the application of brenuk insecticide at 0,5 litre/ha in EC as well as WP formulations were efective in the decreasing of attack intensity of E. flavescens, as well as the population of Empoasca to the extend of 69,99% and 63,63% respectively. Indirectly, these treatments could increase the shoot production of tea plant.